1997
DOI: 10.1002/elps.1150180920
|View full text |Cite
|
Sign up to set email alerts
|

Applications of microsatellite‐based Y chromosome haplotyping

Abstract: Y-chromosomal microsatellites have been investigated for the purposes of application to male identification, population genetics and population history. With nine markers, every male in a German population sample (n = 70) could be identified by an individual-specific Y microsatellite haplotype. The analysis of 474 unrelated males of nine human populations with seven markers revealed 301 different Y haplotypes. The analysis of molecular variance (AMOVA) approach was used to detect male population characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 28 publications
2
38
1
6
Order By: Relevance
“…All individuals tested negative for the Y Alu insert (DYS287). A complete description of the Ychromosome STR loci can be found in Kayser et al (1997). A table of the biallelic Y-chromosome haplotype frequencies in the upper, middle, and lower castes is available at http:// www.genome.org/supplemental/.…”
Section: Y-chromosome and Autosomal Polymorphismsmentioning
confidence: 99%
“…All individuals tested negative for the Y Alu insert (DYS287). A complete description of the Ychromosome STR loci can be found in Kayser et al (1997). A table of the biallelic Y-chromosome haplotype frequencies in the upper, middle, and lower castes is available at http:// www.genome.org/supplemental/.…”
Section: Y-chromosome and Autosomal Polymorphismsmentioning
confidence: 99%
“…The PCR reactions were performed according to the conditions described by Kayser et al (1997) and products separated using 10% denaturing polyacrylamide gel electrophoresis and visualized by silver staining (Sanguinetti et al, 1994). Allele designations were determined by comparison of the sample fragments with those of control DNA samples previously cloned and sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the Y-STR loci DYS19, DYS390, DYS391, DYS392 and DYS393 (Kayser et al, 1997) using blood samples taken from the individuals in our sample, DNA being extracted by an adaptation of the protocol of Higuchi (1989). The PCR reactions were performed according to the conditions described by Kayser et al (1997) and products separated using 10% denaturing polyacrylamide gel electrophoresis and visualized by silver staining (Sanguinetti et al, 1994).…”
mentioning
confidence: 99%
“…(a) the unequivocal reconstruction of its phylogeny as revealed by non-recurrent single nucleotide (SNP) or indel binary polymorphisms; 5,7,8 (b) the abundance of microsatellite markers which reveal additional diversity within SNP-defined lineages (haplogroups); [9][10][11] and (c) the effectiveness with which this chromosome is able to detect population structuring better than either autosomal or mitochondrial markers. 12,13 Through a combination of Y-chromosomal binary and microsatellite markers, Malaspina et al 14 have shown peculiar geographic distributions of certain lineages across Europe, suggesting that Central Europe might be the area where some of these lineages undergo the sharpest changes in frequencies.…”
Section: Introductionmentioning
confidence: 99%